2020
DOI: 10.22271/chemi.2020.v8.i1aq.8694
|View full text |Cite
|
Sign up to set email alerts
|

Promoting seedling growth in Kagzi lime through pre-sowing treatments

Abstract: An experiment was conducted to study the effect of gibberellic acid on seedling growth in Kagzi lime at Regional Horticultural Research Station, Navsari Agricultural University, Navsari during the year 2016-17. The experiment was laid out in a Completely Randomized Design with factorial concept with sixteen treatments and three repetitions. Freshly extracted kagzi lime seeds (S1) and those stored for 15 days (S2) were soaked for 12 hours (D1) and 24 hours (D2) in aqueous solution of gibberellic acid at differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…Additionally, this treatment led to the tallest seedlings (30.02 cm), the highest leaf count (28.62), and the greatest dry weight of shoots (10.04 g) fresh weight (20.60 g) at 180 days after sowing (DAS). Similarly, Chaudhary et al, (2020) [6] explored various pre-sowing treatments for Kagzi lime seeds, focusing on soaking durations of 24 hours and 12 hours in aqueous solutions of gibberellic acid (GA 3 ) at 200 ppm to 500 ppm. The findings revealed that the 12-hour soaking duration consistently outperformed the 24-hour duration across all treatments.…”
Section: Effect Of Pre-sowing Treatments On Germination Percentage An...mentioning
confidence: 99%
“…Additionally, this treatment led to the tallest seedlings (30.02 cm), the highest leaf count (28.62), and the greatest dry weight of shoots (10.04 g) fresh weight (20.60 g) at 180 days after sowing (DAS). Similarly, Chaudhary et al, (2020) [6] explored various pre-sowing treatments for Kagzi lime seeds, focusing on soaking durations of 24 hours and 12 hours in aqueous solutions of gibberellic acid (GA 3 ) at 200 ppm to 500 ppm. The findings revealed that the 12-hour soaking duration consistently outperformed the 24-hour duration across all treatments.…”
Section: Effect Of Pre-sowing Treatments On Germination Percentage An...mentioning
confidence: 99%